A New Proof of Central Limit Theorem for i.i.d. Random Variables - Zhaojun Zong; Feng Hu (Abstract and Applied Analysis)
Central limit theorem (CLT) has long and widely been known as a fundamental result in probability theory. In this note, we give a new proof of CLT for independent identically distributed (i.i.d.) random variables. Our main tool is the viscosity solution theory of partial differential equation (PDE).